NATURE, REALITY, AND THE SACRED: A MEDITATION IN SCIENCE AND RELIGION - Gilkey, Langdon (Zygon, 1989)
Many scientists now recognize the participation of the knower in the known. Not many admit, however, that scientists rely upon intuitions about reality commonly attributed to philosophy and religion: that sensory experience relates us to an order in nature congruent with our minds and of value congruent with our fulfilled being. Nature has disclosed itself to scientists—albeit fragmentarily—as power, life, order, and unity or meaning. In science these remain limit questions, raised but unanswered. In the unity of these qualities, assumed by science, the sacred begins to appear. Addressing the limit questions, not only of scientific but of human experience, is the province of philosophy and religion.